2019
DOI: 10.7567/1347-4065/ab09da
|View full text |Cite
|
Sign up to set email alerts
|

GaN growth via tri-halide vapor phase epitaxy using solid source of GaCl3: investigation of the growth dependence on NH3 and additional Cl2

Abstract: Gallium nitride (GaN) growth via a tri-halide vapor phase epitaxy method using a solid source of GaCl3 and gaseous NH3 was investigated both on Ga-polar and N-polar GaN templates. The relationship between gallium precursor molecule and growth polarity was clarified; it was found that a small amount of GaCl3 could be reduced by H2 originating from the decomposition of NH3 to produce GaCl, and additional Cl2 could suppress the reduction process. Accordingly, GaCl3 was found to be a proper Ga precursor for N-pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…One is vaporization of solid GaCl 3 , which has a high vapor pressure (4500 Pa at 100 °C), and a high flow rate can be easily obtained. Several groups including ours [29][30][31] have reported high-speed growth of GaN with rates of about 10-50 μm h −1 by this method. Another method is the synthesis of GaCl 3 by the reaction of metallic gallium with Cl 2 gas.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…One is vaporization of solid GaCl 3 , which has a high vapor pressure (4500 Pa at 100 °C), and a high flow rate can be easily obtained. Several groups including ours [29][30][31] have reported high-speed growth of GaN with rates of about 10-50 μm h −1 by this method. Another method is the synthesis of GaCl 3 by the reaction of metallic gallium with Cl 2 gas.…”
mentioning
confidence: 87%
“…Cluster formation is also important during VPE growth of GaN. 30) Especially in THVPE with an external precursor gas supply system, a highly concentrated precursor gas can be provided. It is important to increase the growth rate; however, this also results in cluster formation.…”
mentioning
confidence: 99%
“…22,23) Other groups have also succeeded in the growth of GaN (000 1 ¯) using GaCl 3 . [24][25][26][27][28] On the other hand, it was reported that the growth rate on Ga-polar GaN(0001) using GaCl 3 is very low (almost zero). 26) This can be explained by unstable chemisorption of GaCl 3 molecules on nitrogen atoms on the (0001) surface because of the steric barrier created by the first chemisorbed GaCl 3 molecules.…”
mentioning
confidence: 99%
“…Recently, Takekawa et al reported an increase in the HVPE growth rate for GaN(0001) using GaCl 3 by increasing the partial pressure of NH 3 . 28) They speculated that GaCl 3 is converted to GaCl by H 2 (GaCl 3 + H 2 → GaCl + 2HCl) generated from the decomposition of NH 3 . It is well known that GaN can be grown using GaCl on a (0001) surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation